The Clinical Assessment in the Legal Field: An Empirical Study of Bias and Limitations in Forensic Expertise - Iudici, Antonio; Salvini, Alessandro; Faccio, Elena; Castelnuovo, Gianluca (Frontiers in Psychology, 2015)
According to the literature, psychological assessment in forensic contexts is one of the most controversial application areas for clinical psychology. This paper presents a review of systematic judgment errors in the forensic field. Forty-six psychological report written by psychologists, court consultants, have been analyzed with content analysis to identify typical judgment errors related to the following areas: a) distortions in the attribution of causality, b) inferential errors, and c) epistemological inconsistencies. Results indicated that systematic errors of judgment, usually referred also as “the man in the street”, are widely present in the forensic evaluations of specialist consultants. Clinical and practical implications are taken into account. This article could lead to significant benefits for clinical psychologists who want to deal with this sensitive issue and are interested in improving the quality of their contribution to the justice system.